Medical Treatment for Peyronie’s Disease: Systematic Review and Network Bayesian Meta-Analysis - Hyun Young Lee; Jong Hyun Pyun; Sung Ryul Shim; Jae Heon Kim (The World Journal of Men's Health, 2024)
Purpose: To investigate the efficacy of medical treatment options for Peyronie's disease (PD) including oral drugs, intralesional treatment and mechanical treatment compared with placebo treatment using network meta-analysis (NMA). Materials and Methods: We searched the randomized controlled trials (RCTs) of PD in PubMed, Cochrane library, and EMBASE up to October 2022. RCTs included medical treatment options: oral drugs, intralesional treatment and mechanical treatment. Studies reporting at least one of the outcome measures of interest including curvature degree, plaque size, and structured questionnaires (International Index of Erectile Function, IIEF) were included. Results: Finally, 24 studies including 1,643 participants met our selection criteria for NMA. There was no statistically significant treatment compared to placebo of the curvature degree, plaque size, IIEF in Bayesian analysis. The SUCRA values of ranking probabilities for each treatment performance, which indicated that hyperthermia device ranked first in NMA. However, in frequentist analysis, 7 of mono treatments (coenzyme Q10 [CoQ10] 300 mg, hyperthermia device, interferon alpha 2b, pentoxifylline 400 mg, propionyl-L-carnitine 1 g, penile traction therapy [PTT], vitamin E 300 mg) and 2 of combination treatments (“PTT–extracorporeal shockwave treatment”, “vitamin E 300 mg–propionyl-L-carnitine 1 g”) were statistically significant for improvement of curvature degree, and 9 of mono treatments (CoQ10 300 mg, hyaluronic acid 16 mg, hyperthermia device, interferon alpha 2b, pentoxifylline 400 mg, propionyl-L-carnitine 1 g, verapamil 10 mg, vitamin E 300 mg, vitamin E 400 U) and 3 of combination treatments ("interferon alpha 2b–vitamin E 400 U", "verapamil 10 mg–antioxidants", “vitamin E 300 mg–propionyl-L-carnitine 1 g”) were statistically significant in the improvement of plaque size. Conclusions: At present, there is no clinical treatment alternatives that have been demonstrated to be effective compared to placebo. Nonetheless, as the frequentist approach has shown that a number of agents are efficacious, further research is expected to develop more effective treatment options.